DUSP1 regulates the JAK2/STAT3 signaling pathway through targeting miR-21 in cervical cancer cells: DUSP1 targets miR-21 to regulate JAK2/STAT3 in CC cells - Chen, Hailin; Ren, Songsen; Wan, Hui; Wei, Wengong; Luo, Yi; Cai, Meiling (Cellular and Molecular Biology, 2023)
This study was to investigate the effect of DUSP1 on cervical cancer (CC) cells by targeting the miR-21 regulatory JAK2/STAT3 signaling pathway. For this purpose, fifteen CC patients treated at our hospital from January 2021 to February 2023 were selected. CC tissues and para-cancerous (PC) tissues were collected from the patients, and DUSP1 protein and mRNA expression levels were detected by Western blot and qPCR. The C33a control group (COG) and DUSP1 overexpression group (OVG) were set up: human cervical squamous carcinoma cells (CSCC) in the C33a COG were cultured without any treatment, while the DUSP1 OVG was cultured using DUSP1 gene overexpression lentivirus infection progeny. The proliferation ability of the three groups of cells was measured by CCK8, protein and mRNA expression by Western blot and qPCR, and cell migration and invasion ability by Transwell. It was found that DUSP1 protein and mRNA in CC tissues were reduced compared with those in PC tissues (P<0.05). The miR-21 in the DUSP1 OVG was reduced than those in the C33a COG (P<0.05). The expression of JAK2, STAT3 mRNA and protein in the DUSP1 OVG were reduced compared with those in the C33a COG (P<0.05). In conclusion, overexpression of DUSP1 can target and reduce the expression of miR-21, block the JAK2/STAT3 signaling pathway, reduce the viability of CC cells, inhibit the proliferation and migration and invasion ability of CC cells, and induce apoptosis of CC cells, thus providing a theoretical basis for the targeted treatment of clinical CC.